1999
DOI: 10.1002/(sici)1097-4644(19991001)75:1<22::aid-jcb3>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of the osteoblast phenotype in primary human osteoblasts in culture: Comparison with rat calvarial cells in osteoblast differentiation

Abstract: In rat osteoblast-like cells, a time-dependent sequence of growth and differentiation-dependent genes has been identified and a model of osteoblast differentiation in culture suggested. We investigated the expression of the bone matrix-associated proteins osteonectin and procollagen I and of the bone cell phenotype-related proteins alkaline phosphatase and osteocalcin during cell culture in primary human osteoblast like cells. Primary human explant cultures from nine young healthy donors were established under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 0 publications
5
58
1
2
Order By: Relevance
“…Lysosomes Colocalize with Procollagen-containing Vesicles in AA-treated Osteoblasts-Enhanced collagen synthesis is a hallmark feature of differentiated osteoblasts (29,39). We investigated extracellular and intracellular collagen production in control and AA-differentiated osteoblasts.…”
Section: Kinesin Mediates Lysosome Dispersion In Aa-treated Mc3t3-e1mentioning
confidence: 99%
“…Lysosomes Colocalize with Procollagen-containing Vesicles in AA-treated Osteoblasts-Enhanced collagen synthesis is a hallmark feature of differentiated osteoblasts (29,39). We investigated extracellular and intracellular collagen production in control and AA-differentiated osteoblasts.…”
Section: Kinesin Mediates Lysosome Dispersion In Aa-treated Mc3t3-e1mentioning
confidence: 99%
“…The effect on cell differentiation was studied by examination of collagen synthesis and alkaline phosphatase (ALP) production. 30,31 After completion of the original study, NO-donating NSAID became available and a preliminary study of their effect on cell number was added as a further comparison.…”
mentioning
confidence: 99%
“…A study showed that isolated rat osteoblasts expressed far less ALP, pro-collagen type I, transforming growth factor-β1 and interleukin 6 (IL-6) when compared to isolated human osteoblasts (Torricelli et al, 2003). There is also evidence that isolated rat osteoblasts respond species-specifically to differentiation factors (Siggelkow et al, 1999), including glucocorticoids in particular (Prince et al, 2001). These differences should be acknowledged when selecting animal cells for studying the interaction of electromagnetic energy and bone.…”
Section: Discussionmentioning
confidence: 99%